Gåtfullhet i sagalitteraturen - Sävborg, Daniel (Scandinavistica Vilnensis, 2014)
The article discusses several aspects of the well-known enigmatic character of the Icelandic family sagas. Four cases are examined in detail: the cause of Unnr’s sorrow in the beginning of Njáls saga, the talk between Stýrr and Snorri in the berserks’ episode in Eyrbyggja saga, the identity of Vésteinn’s murderer in Gísla saga, and Guðrún’s enigmatic last words about her love in Laxdoela saga. The use of the enigmatic narrative form in all these cases is discussed. The article argues that this kind of enigmatic episodes in the saga literature should not be interpreted in the same way as enigmatic episodes in modern literary works, where the solution of the mystery is left open. In the sagas, the mystery has a solution, and there is a correct answer. In contrast to modern literature, the mystery in the sagas can always be solved, and the use of enigmas and mysteries is rooted in the literary technique of the sagas. The article analyses and proposes several reasons for the enigmatic narrative style used by the saga authors.
Keywords: enigmas in Icelandic family sagas; Njáls saga; Eyrbyggja saga; Gísla saga; Laxdœla saga; narrative style in sagas